Avaliação de desempenho organizacional em redes de cooperação - Tavares, Carlos Eduardo Moreira (2008)
The present study has as objective to propose a tool of acting evaluation for the nets of business cooperation based on Balanced Scorecard. It is verified that the acting evaluation in this organizational model differs of the traditional models in function of their characteristics, where the acting is resulted of the performance together of their associates and it requests the search of information among the participant companies. In this sense it was sought starting from Adam study (2006), on acting indicators in cooperation nets, to accomplish a comparative analysis among the technicians' of the programs cooperation nets perception and of the participant cooperation nets of VIAREDES on the importance of the group of indicators presented in the study. After it analyzes it of the perceptions was possible to accomplish the adaptation of Balanced Scorecard four perspectives in agreement with the characteristics presented by the nets of companies. As result was verified that the perception of importance as much of the technicians of the Program Reds of Cooperation of the State of Rio Grande do Sul as of the researched nets they were similar, evaluating the group of indicators studied as relevant for the acting of this organizational model. This result provided to the adaptation of Balanced Scorecard perspectives tends as addressing the characteristics of the cooperation nets and the studied indicators. It was observed that the acting evaluation starting from this tool is possible of being accomplished, being necessary some adjustments in relation to the segment and load of the net that it be applied.